2017
DOI: 10.1186/s40168-017-0348-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of temperature, organic carbon, and pipe material on microbiota composition and Legionella pneumophila in hot water plumbing systems

Abstract: BackgroundSeveral biotic and abiotic factors have been reported to influence the proliferation of microbes, including Legionella pneumophila, in hot water premise plumbing systems, but their combined effects have not been systematically evaluated. Here, we utilize simulated household water heaters to examine the effects of stepwise increases in temperature (32–53 °C), pipe material (copper vs. cross-linked polyethylene (PEX)), and influent assimilable organic carbon (0–700 μg/L) on opportunistic pathogen gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 66 publications
5
83
1
Order By: Relevance
“…Each SPPR was equipped with either eight pieces of 20 mm × 10 mm cross-sectional PEX (n = 18) or solid copper (n = 18) pipe material. Pipe coupons had been aged in the bottles for six years in prior experiments, described elsewhere [ 8 , 9 , 10 , 27 ], which provided a benefit of well-aged premise plumbing pipe materials and mature biofilms at the start of the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each SPPR was equipped with either eight pieces of 20 mm × 10 mm cross-sectional PEX (n = 18) or solid copper (n = 18) pipe material. Pipe coupons had been aged in the bottles for six years in prior experiments, described elsewhere [ 8 , 9 , 10 , 27 ], which provided a benefit of well-aged premise plumbing pipe materials and mature biofilms at the start of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…However, lower LD incidence associated with residential exposure was noted from August 2015 onwards and our sampling during this period revealed undetectable or very low levels of L. pneumophila in residential plumbing [ 1 , 3 ]. While temporal associations between the switch in water supply with reduced levels of chlorine, high levels of iron, elevated temperature for Flint River water, and the resulting outbreak of LD were predictable based on prior work [ 7 , 8 , 9 , 10 ], and duly noted for the Flint outbreak [ 1 , 3 , 5 ], precise patterns of the outbreak in relation to large health care facilities versus residential single family homes are still the subject of scientific and public interest [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gomez-Alvarez et al (2016) found that the onset of severe nitrification resulted in increases in total biomass in the system [110]. The increase in biomass and concentrations of bacteria during nitrification are likely partially explained by the assimible organic carbon (AOC) introduced to the system as a result of nitrification [111][112][113]. Increases in AOC along, however, have not been shown to cause increased concentrations of OPPP, indicating the importance of other nitrification side-effects on the increased growth of OPPP seen during nitrification events [109,112,113].…”
Section: Microbial Regrowth and Opportunistic Premise Plumbing Pathogensmentioning
confidence: 99%
“…The increase in biomass and concentrations of bacteria during nitrification are likely partially explained by the assimible organic carbon (AOC) introduced to the system as a result of nitrification [111][112][113]. Increases in AOC along, however, have not been shown to cause increased concentrations of OPPP, indicating the importance of other nitrification side-effects on the increased growth of OPPP seen during nitrification events [109,112,113]. Given the lack of inactivation of NTM after the introduction of chloramines, reintroduction of chloramines into premise plumbing systems after periods of stagnation and minimal chloramine residual, that promoted growth of NTM, may not be able to control the growth and release of these pathogens [108].…”
Section: Microbial Regrowth and Opportunistic Premise Plumbing Pathogensmentioning
confidence: 99%
“…For example, a chronic exposure to some fungi can cause asthma, but early life exposure to various mold and its derivatives can protect children from allergic and autoimmune diseases[3]. A growing number of studies have helped us estimate the microbial diversity in various indoor environments, and revealed that microbial diversity is closely related to the geographic locations[4], weather conditions[5, 6], populations[7], functions[8], and internal ventilation conditions[9].…”
Section: Introductionmentioning
confidence: 99%